Create a Traffic Control Information Space in the Logistics Environment - BAKYT, Gabit B.; SEIDEMETOVA, Zhanerke S.; ABDULLAYEV, Seidulla S.; ADILOVA, Nazdana J.; KAMZINA, Azhar D.; AIKUMBEKOV, Muslim N. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The research describes the competitive environment in the market of transport-logistics services of Kazakhstan. Logistics networks are represented by two transport systems: JSC ‘National Company Kazakhstan Temirzholy’ hereinafter Operator, as well as other railway administrations and access routes of the Customer (LLP ‘KM Tranko). The experience of TRANKO JSC, where marketing systems in the railway services market of Kazakhstan occupy an important place, is of interest. This format of services in the Republic is not common, therefore the services of JSC ‘TRANKO’ are unique and the specifics of these services, including planning and management of the logistics process with a system of response to failures, can be provided only for large business.